Optimal Control Applied to Marine Eco-Epidemiological model with Disease in Prey Species - Hasan, S.M. Mahathy; Biswas, Md. Haider Ali; Andallah, Laek Sazzad (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, the purpose of the work is to modified of an Eco-epidemiocal model and analysis with the optimal control strategies for the infected prey. Furthermore, the dynamical behaviors, i.e. the positivity, boundedness, stability and Hopf bifurcation of the proposed model are investigated. The optimal control theory is applied to control the effect of disease on prey population and plays a vital role to eliminate disease from prey population.The results obtained suggested the optimal control is ensuring the prey-predator populations coexists in a defined habitat.